Risk Factors for Decreased Pelvic Floor Muscle Strength: Which is More Effective? - Omer Demir; Cihan Comba (Gynecology Obstetrics & Reproductive Medicine)
Objective: The aim of this study was to assess whether cigarette smoking weakens the pelvic floor and to determine its effective impact relative to other factors.